Challenges of Translating Metonymy in the Qur'ân with Reference to Some Selected Verses from the Cow and Women Chapters - Elsayed, Ramadan (International Journal of Linguistics and Translation Studies, 2025)
This study attempts to explore the challenges that translators of the Qur'ân may face when translating metonymy in the Qur'ân into English. The samples selected for analysis include the translation of 12 Qur'ânic verses from the Cow and Women Chapters from three Qur'ân translations: Hilâlî and Khân (1996), Ghâli (2003), and Abdel Haleem (2004). The study adopts a qualitative descriptive research methodology that depends on collecting qualitative data and analyzing them within the framework of pragmatics (Grice's Conversational Maxims), skopos theory, and Qur'ânic exegeses. The study findings show that translating metonymy in the Qur'ân is a problematic challenge requires a translator who is well-versed about both languages' peculiarities and culture particularities. Also, it is significant that reliable Qur'ân exegeses have to be consulted while translating metonymy in order to avoid mistranslations and inappropriate explanations. Furthermore, metonymy may be misunderstood due to the translator’s unawareness of its embedded meaning. The study concludes that intolerable mistakes may occur if the translator renders metonymy literally. So, the functional approach is preferable to be adopted in translating such structures. Moreover, metonymy may be used to talk about offensive and taboo issues in a refined and elevated style. Therefore, it is the role of the translator to transfer the implied meaning of metonymy using the same or the approximate refined style. Accordingly, the translator is, sometimes, forced to add explanations for the metonymy in footnotes, endnotes or a glossary when the metonymy is Qur'an-specific and has no equivalent in the TL.